Answer to Question #29210 in Algebra for judy hallak
Let's subtract the first equation from the second:
2x=-4 whence x=-2
Now we can find y. Consider the first equation:
4y=-6-6=-12 whence y=-3
So the answer is (-2,-3)
We can verify obtained answer by substituting it into initial system:
3*(-2)-4*(-3)=6& <=> -6+12=6& <=> 6=6
5*(-2)-4*(-3)=2& <=> -10+12=2& <=> 2=2
We obtained right equalities hence our answer is correct because it turns the initial system into right equalities.
Need a fast expert's response?Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!